PEMANFAATAN PAKAN CAMPURAN MINYAK JELANTAH UNTUK MENINGKATKAN PERTUMBUHAN IKAN GURAMI SEBAGAI RANCANGAN BOOKLET PADA PEMBELAJARAN BIOLOGI SMA KELAS X (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the effect of using used cooking oil in the composition of feed on the growth of gouramy and to determine the best percentage of used cooking oil in feed to increase the growth of gouramy, as well as to produce a booklet design as a teaching material in biology learning in class X SMA. This study consisted of two stages, namely the experiment and the design of the booklet in February-September 2020. The experiment was with a randomized block design (RBD) and used 4 treatments with 3 replications. The treatments were given in the form of different used cooking oil doses, including: P0 (control treatment), P1 (3% used cooking oil), P2 (6% used cooking oil), and P3 (9% used cooking oil). The parameters measured included absolute weight growth, relative growth, feed conversion, and fish survival rate. The results showed that the difference in used cooking oil dose had a very significant effect (p <0.01) on absolute weight growth, relative growth, feed conversion and had no significant effect (p> 0.05) on fish survival. The 9% used used cooking oil treatment was the best research treatment which resulted in an absolute weight growth of 5.34 g, a relative growth rate of 133%, and a feed conversion of 2.62. P3 resulted in growth almost close to P0 (control treatment). The survival rate of gouramy during maintenance ranges from 86.67-100%. The experimental results are used for booklets as teaching materials on waste material and waste handlers for learning biology in class X high school.Key Words : Booklet , Gouramy Fish, Used Cooking Oil, Growth